Meningkatkan Promosi Produk Melalui Instagram Untuk UMKM Di To’ Pao Toraja Utara - Lisa K Wibisono; Rati Pundissing; Dwibin Kannapadang (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
This service aims to develop effective strategies to increase product promotion for Micro, Small and Medium Enterprises (MSMEs) through the Instagram platform. In the current digital era, Instagram has become one of the most popular and influential marketing tools, especially for MSMEs who want to expand their market reach. Through a literature review and analysis of best practices in digital marketing. Creating interesting content, using relevant hashtags, and implementing effective promotional strategies. By involving MSMEs directly in the strategy development process, this research also aims to strengthen their involvement in digital marketing and increase their understanding of the importance of online product promotion.